The Model of School Preparation for Implementing the Federal State Educational Standards of the Second Generation - A. S. Sidenko (Obrazovanie i Nauka, 2015)
Nowadays, the new educational standards of the second generation are being developed and implemented at all levels of school education. The above stan- dards define the social profile of the first year pupil, as well as the ones of the primary, secondary and high school leavers. The authors describe the components of manage- rial pedagogic model of the future teachers training, which complies with the task of implementing the new educational standards; the levels of such training being defined as beginners, basic and advanced. The model in question is based on the combination of intra-school professional upgrading of managerial and pedagogic staff, their self- development and the self-training course implying the activity component. For any form of staff professional development in educational sphere, both internal and exter- nal resources should be applied, their list being provided